2014
DOI: 10.3368/jhr.49.3.634
|View full text |Cite
|
Sign up to set email alerts
|

Children of War

Abstract: A B S T R A C TThis paper provides causal evidence on the long-term consequences of large-scale physical destruction on educational attainment, health status, and labor market outcomes of children. I exploit the plausibly exogenous region-by-cohort variation in the intensity of World War Two (WWII) destruction as a unique quasi-experiment. I fi nd that exposure to destruction had long-lasting detrimental effects on the human capital formation, health, and labor market outcomes of Germans who were at school-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A few recent studies have started to produce robust support for damaging effects on physical and cognitive development outcomes as an adult have been reported from various other conflict-affected settings, e.g. Cambodia, Germany, Mozambique and Zimbabwe (de Walque, 2006;Akbulut-Yuksel, 2014;Domingues and Barre, 2013;Alderman, Hoddinott and Kinsey, 2006). The important study by provides convincing evidence that the magnitude of adverse impacts may vary significantly by age at exposure 40 years after the end of the conflict.…”
Section: Long-term Consequences Of Early-life Exposure To Conflictmentioning
confidence: 90%
“…A few recent studies have started to produce robust support for damaging effects on physical and cognitive development outcomes as an adult have been reported from various other conflict-affected settings, e.g. Cambodia, Germany, Mozambique and Zimbabwe (de Walque, 2006;Akbulut-Yuksel, 2014;Domingues and Barre, 2013;Alderman, Hoddinott and Kinsey, 2006). The important study by provides convincing evidence that the magnitude of adverse impacts may vary significantly by age at exposure 40 years after the end of the conflict.…”
Section: Long-term Consequences Of Early-life Exposure To Conflictmentioning
confidence: 90%
“…Therefore, historic events that occur during an individual's school‐age years will potentially have a profound impact on their behaviour and thinking. There is a growing concern among economists that economic conditions and special experiences early in life may have persistent effects on health, schooling and socioeconomic outcomes later in life (Akbulut‐Yuksel, 2014; Glewwe et al., 2001; Lee, 2014). Many studies have examined the impacts of conflict on human capital, either in terms of educational or health outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found evidence of the negative impact of conflicts on health in children exposed to these conflicts. Moreover, Akbulut‐Yuksel (2014) noted a significant, long‐lasting detrimental effect on human capital formation, health and labour market outcomes of Germans who were of school age during World War II – they had 0.4 fewer years of schooling on average, were half an inch shorter and had lower self‐reported health satisfaction in adulthood, while their future labour market earnings decreased by 6% on average due to exposure to wartime physical destruction. Baez (2011) investigated the indirect impact of civil conflict and found that the negative impacts of childhood exposure at the onset of the refugee migration caused by the conflict persisted over time, both in terms of educational and health outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach tends to overlook the possible substitution between different types of food. While some studies delve into the nutritional dimensions of food insecurity (Akbulut‐Yuksel, 2014; Akresh et al., 2012; Bundervoet et al., 2009; Gordon & Halileh, 2012; Kumar & Quisumbing, 2013; Minoiu & Shemyakina, 2014), a comprehensive theoretical framework for effectively assessing trade‐offs among various food groups at the time of conflicts warrants further exploration. Conflict‐induced uncertainty alters household expenditures and preferences toward staple food consumption (Rockmore, 2020).…”
Section: Introductionmentioning
confidence: 99%